Increased Carotid Intima-Media Thickness (IMT) in Hyperuricemic Individuals May Be Explained by Hyperhomocysteinemia Associated with Renal Dysfunction: a Cross-Sectional Study - Park, Ji Ho; Song, Jung Soo; Choi, Sang Tae (Journal of Korean medical science, 2019)
Both hyperuricemia and hyperhomocysteinemia are known as main risk factors of cardiovascular diseases. There has been, however, no report on the relationship between carotid intima-media thickness (IMT) and homocysteine (Hcy) in hyperuricemic patients. This study aimed to investigate how hyperuricemia is associated with increased carotid IMT with a focus on hyperhomocysteinemia. This cross-sectional study included 1,222 patients who visited the Chung-Ang University Hospital Health Promotion Center from January 2013 to December 2015. The serum Hcy levels were estimated with a competitive immunoassay using the direct chemiluminescence method. The carotid IMT was measured by B-mode carotid ultrasonography. The definition of hyperuricemia was a serum uric acid level > 7.0 mg/dL for men or > 5.6 mg/dL for women, and hyperhomocysteinemia was defined as serum levels > 15 μol/L. The hyperuricemic patients showed significantly higher serum Hcy levels and lower estimated glomerular filtration rate (eGFR) than did normouricemic patients (13.39 ± 4.42 vs. 11.69 ± 3.65 μol/L, P < 0.001; 85.16 ± 19.18 vs. 96.14 ± 16.63, < 0.001, respectively). Serum Hcy level (odds ratio [OR], 1.050; 95% confidence interval [CI], 1.009-1.092) and fasting glucose level (OR, 1.018; 95% CI, 1.011-1.026) were independent risk factors for carotid plaque. In patients with hyperuricemia, the serum Hcy levels correlated with the eGFR (γ = -0.478, < 0.001). The carotid IMT correlated with serum Hcy levels and eGFR (γ = 0.196, = 0.008; γ = - 0.297, < 0.001, respectively) but not with the serum lipid profile. These results suggest that renal function impairment in hyperuricemic patients may worsen carotid IMT by increasing serum Hcy levels.